Legislative amendments regarding criminal proceedings under martial law - V. V. Ablamska (Law and Safety)
The issue of legal regulation of the specifics of criminal proceedings under martial law has been studied. When posing the problem, it was stated that Russia’s full-scale war against Ukraine significantly changed the functioning of state bodies and institutions, as a result of which appropriate changes and additions were made to a number of normative legal acts. This also affected the specifics of the procedure for conducting pre-trial investigation and court proceedings under martial law. A systematic analysis of the provisions of the CCP of Ukraine shows that certain innovations are quite debatable and controversial. In this perspective, the need to eliminate legislative conflicts in order to implement effective and unambiguous practical implementation of legislative norms is argued. The key aspects in ensuring the practical application of the norms of the criminal procedural legislation of Ukraine regarding the specifics of criminal proceedings under martial law should be the regulation of the specified issue in a single section. This statement has been made as a result of a systematic analysis of the Criminal Procedure Code of Ukraine, in particular, it was found that changes and additions were made not only to Section IX-1 “Special regime of pre-trial investigation, trial under martial law conditions”, but also to other general provisions of the Criminal Procedure Code of Ukraine.